Concrete expressions : brutalism and the government buildings precinct, adelaide (2013)
The Architecture Museum in the School of Art, Architecture and Design at the University of South Australia houses a unique research collection based largely on donations of items from South Australian based private practitioners who worked in the twentieth century. Diverse in composition, the material provides a rich and unparalleled resource for research into the state’s social and cultural history through the lens of architecture and the built environment. A key goal of the Architecture Museum is to foster such research and to encourage scholarly publications as an outcome of researchers’ investigations. The Museum relies on grants and external sponsorship to create research opportunities. Consequently it is delighted to have the generous support of the South Australian Department of Environment, Water and Natural Resources (DEWNR) through the SA Built Heritage Research Fellowship at the Architecture Museum. Kevin O’Sullivan, the DEWNR SA Built Heritage Research Fellow 2012/13, focussed his research on a cohesive group of four government buildings constructed in Adelaide during the 1970s. Designed by different architects, the buildings all feature the overt expression of their concrete materiality and, as a group, form a distinctive architectural and urban design precinct in the central business district. The four buildings are often referred to as ‘Brutalist’ in style. What is meant by Brutalism? Concrete Expressions explores that question and analyses whether or not the buildings are in fact Brutalist. It also considers their role as a governmental ensemble and analyses their contribution from an urban design perspective. In addition to its stylistic focus, the monograph raises considerations about the appreciation of Brutalist buildings which, like other styles of the second half of the twentieth century, are increasingly attracting community, professional and academic attention. The Architecture Museum is very pleased to be associated with the publication of Concrete Expressions.